Treatment and management of cognitive dysfunction in patients with multiple sclerosis - DeLuca, John; Chiaravalloti, Nancy D; Sandroff, Brian M (Nature reviews. Neurology, 2020)
Cognitive impairment is a common and devastating manifestation of multiple sclerosis (MS). Although disease-modifying therapies have been efficacious for reducing relapse rates in MS, such treatments are ineffective for treating cognitive dysfunction. Alternative treatment approaches for mitigating cognitive problems are greatly needed in this population. To date, cognitive rehabilitation and exercise training have been identified as possible candidates for treating MS-related cognitive impairment; however, cognitive dysfunction is still often considered to be poorly managed in patients with MS. This Review provides a comprehensive overview of recent developments in the treatment and management of cognitive impairment in people with MS. We describe the theoretical rationales, current states of the science, field-wide challenges and recent advances in cognitive rehabilitation and exercise training for treating MS-related cognitive impairment. We also discuss future directions for research into the treatment of cognitive impairment in MS that should set the stage for the inclusion of cognitive rehabilitation and exercise training into clinical practice within the next decade.